Evaluasi motivasi kerja sumber daya manusia dalam upaya peningkatan kinerja sumber daya manusia desa - Kania Wulandari; Salsadilla Rihhadatul Aisy Putri Alamsyah (ARKA INSTITUTE, 2022)
The purpose of this study was to analyze the potential of human resources and their management in an effort to improve the performance of human resources in Nagrak Village, Pacet District, Bandung Regency. The method used is a qualitative method, where the application is to use primary data by seeking information directly from sources by using interviews and data analysis in the field using the Miles and Huberman model (data reduction, data presentation, verification). Based on the results of the analysis and discussion, it can be concluded that based on the Performance Analysis of the Village Head, it is sufficient to improve employee performance, only in terms of assigning tasks/jobs it is still not fair. And in general, the quality of Village Apparatus HR in managing Nagrak Village is quite adequate but really needs to be improved.